Urgensi Akta Perjanjian Kerja Sama Notaris dalam Bisnis Waralaba ditinjau dari Pasal 1245 KUH Perdata - Ahmad Naufal Qois; Habib Adjie (Fakultas Hukum Universitas Narotama, 2023)
The COVID-19 pandemic has had a significant impact on business activities related to logistics access, which had stalled, resulting in potential non-fulfillment of obligations in business contracts. In the franchise business, there are many unilateral agreements that must be obeyed by business partners. Most of the people agree to the agreement that has been made unilaterally by the franchisor or franchisor. This research method uses a normative juridical approach, carried out with analytical descriptive analysis of juridical studies on authentic deeds, notarial cooperation agreements, franchise businesses and overmacht (Article 1245 of the Civil Code). The technique of collecting legal materials is done by studying literature, browsing internet materials in the form of articles and scientific journals. The urgency of the notary cooperation agreement deed in the franchise business is the legal basis to protect the rights and obligations of the parties. Article 1245 of the Civil Code provides legal protection for parties involved in the deed of agreement. An authentic deed becomes a technical step related to legal remedies that are carried out in the event of a compelling situation experienced by one of the parties in a franchise business agreement. Keywords: Urgency, Notarial Cooperation Agreement, Franchise Business, Article 1245 of the Civil Code